Nerve Growth Factor-Based Therapy in Alzheimer’s Disease and Age-Related Macular Degeneration - Amadoro, Giuseppina; Latina, Valentina; Balzamino, Bijorn Omar; Squitti, Rosanna; Varano, Monica; Calissano, Pietro; Micera, Alessandra (Frontiers in Neuroscience, 2021)
Alzheimer’s Disease (AD) is an age-associated neurodegenerative disease which is the most common cause of dementia among the elderly. Imbalance in nerve growth factor (NGF) signaling, metabolism and/or defect in NGF transport to the basal forebrain cholinergic neurons occurs in patients affected from AD. According to the cholinergic hypothesis, an early and progressive synaptic and neuronal loss in basal forebrain vulnerable population involved in memory and learning processes leads to degeneration of cortical and hippocampal projections followed by cognitive impairment with accumulation of misfolded/aggregated A and tau protein. The neuroprotective and regenerative effects of NGF on cholinergic neurons have been largely demonstrated, both in animal models of AD and in living patients. However, the development of this neurotrophin as disease-modifying therapy in humans is challenged by both delivery limitations (inability to cross the blood-brain barrier, poor pharmacokinetic profile) and unwanted side-effects (pain and weight loss). Age-related Macular Degeneration (AMD) is a retinal disease which represents the major cause of blindness in developed countries and shares several clinical and pathological features with AD, including alterations in NGF transduction pathways. Interestingly, nerve fiber layer thinning, degeneration of retinal ganglion cells and changes of vascular parameters, aggregation of A and tau protein and apoptosis also occur in the retina of both AD and AMD. A protective effect of ocular administration of NGF on both photoreceptor and retinal ganglion cell degeneration has been recently described. Besides, the current knowledge about the detection of essential trace metals associated with AD and AMD, and their changes depending on severity of diseases, either systemic and locally detected, further pay the way for promising diagnostic approach. This review is aimed at describing the employment of NGF as common therapeutic approach to AMD and AD and the diagnostic power of detection of essential trace metals associated with both diseases. The multiple approaches employed to allow a sustained release/targeting of NGF to brain and its neurosensorial ocular extensions will be also discussed, highlighting innovative technologies and future translational prospects